The hELENa project: II. Abundance distribution trends of early-type galaxies; from dwarfs to giants - Sybilska, Agnieszka; Lisker, Thorsten (Monthly notices of the Royal Astronomical Society, 2018)
In this second paper of The role of Environment in shaping Low-mass Early-type Nearby galaxies (hELENa) series we study [Mg/Fe] abundance distribution trends of